Is Corn Stover Harvest Predictable Using Farm Operation, Technology, and Management Variables?. (1st March 2018) - Obrycki, John F.; Karlen, Douglas L.
Abstract : Core Ideas: Corn stover removal was not common in 2010. Crop sequences were similar for stover and non‐stover harvest farms. State‐level variation occurred in the relative size of farms removing corn stover. Soil erosion control measures were not frequently adopted by either farm group. Crop residue management, provision of animal feed or bedding, and increased income are potential reasons for harvesting corn ( Zea mays L.) stover. Reasons for not doing so include the need for crop residue to restore or increase soil organic matter, protect against wind and water erosion, and cycle plant nutrients. Bioenergy market development may increase the number of producers harvesting corn stover. Can farming practice data predict the likelihood for harvesting corn stover at a national scale? Farm operation, technology, and management variables from the 2010 Agricultural Resource Management Survey (ARMS) of U.S. corn growers were compared between operations that removed corn stover and those that did not. Nationwide, stover was removed from approximately 6.3% of all corn operations, indicating stover harvest was not a common practice in 2010. Factors increasing the likelihood for stover harvest included producing feed corn, managing crop residues for pest control, and farmland ownership. Technology and conservation practice adoption rates were similar in both groups. Excessive stover removal can increase soil degradation. Both groups had erosion control adoption rates of ≤10%, which may provide an additional disincentive to harvest stover. Overall, the evaluated variables were similar between producers that did and did not harvest stover. This assessment provides a 2010 national baseline that can be used for future evaluations as bioenergy and bioproduct markets develop.